Vocational School Students' Engagement in Learning Reading Comprehension Using Story Mapping Technique - Aqilah, Drupadi Sana; Hakim, Putri Kamalia (Peneliti.net, 2024)
This research aims to find out how story mapping engages students in learning reading comprehension and their responses to it. This research is a qualitative research with a descriptive case study research design. The participants of this study are tenth grade students at vocational high school. Data collection in this research used observation and interview. The researcher used the theory of (Braun & Clark 2006) to analyze the data. The results reported that story mapping could engage students in learning reading comprehension through behavioral, cognitive, and emotional. The students also showed positive responses to the use of story mapping in the classroom. It indicates that story mapping is an appropriate technique to use.